“Beliefs and practices in teaching efl writing in high schools” - Carvajal Jácome, Claudia Liset (2024)
The present study “Beliefs and practices in teaching EFL Writing in high schools” has features of a survey research design besides. The objective was to describe teachers’ beliefs and practices in teaching writing in high schools of the Cusco - Perú. Therefore, a quantitative descriptive approach was used to collect and analyze data through a survey applied to twenty-one EFL teachers situated in the Province de Cusco, Department of Cusco, - Perú. Indeed, the Cusco city was selected with the criteria of convenience sampling because of the accessibility to the English teachers’ coordinator to ask for the authorization. Moreover, data was analyzed by SPSS 20.0. As a result of the study showed that there is a strong consensus among respondents, endorsing writing as a cognitive process-based activity and favoring its role as a form-based activity. Thus, this collective perspective emphasizes the significance of writing as a tool for learning and practicing linguistic structures, coupled with the application of specific textual genre features through controlled composition tasks. Moreover, participants advocate for teachers to assume a dual role as transmitters and facilitators in the writing instructional process. Finally, the majority of high school instructors adopted the principles (activities, strategies) of the product approach and process approach to teach writing.